Optimizing The Implementation of Sirekap Application Disturbances in the 2024 Election - Tasya Adelia (International Journal of Students Education, 2024)
Optimizing the implementation of sirekap application interference in the 2024 election has an important role in the general election process (election). The election results have been announced (2024) the recapitulation of the election results has been cheated. This writing method uses (Riveuw Literature). The voting process also needs to be carried out officially. The Sirekap application can also be used officially and can also be viewed via the website. Unfortunately, at the time of voting, the KPU confirmed that the voting results were fraudulent and failed, so that's why the results were declared a failure and this is also what makes the public not trust the election results that have been issued or determined and also Ihsan Maulan also said, it is not surprising that the public is worried and asking questions about the results of the 2024 elections. Investment in development is needed. technology and training aims to ensure that sirekap can function effectively, it also requires backup and technical support that can overcome disruptions or failures experienced during voting.